Peacebuilding after war and violence - Neighbourhood matters - Selman Almohamad; Markus Kirchschlager; Sabine Kurtenbach (German Institute of Global and Area Studies (GIGA), 2020)
Sustainable Development Goal 16 on "peace, justice, and strong institutions" is widely considered a central pillar of sustainable development. Based on a comprehensive concept of peace that goes beyond the mere absence of war, it might also be the most difficult to realise. Debates in Peace and Conflict Studies have followed other Social Science debates in exiting the "national container," namely by focusing on the interaction between global and subnational or local dynamics. However, the regional dimension is no longer acknowledged as an important intervening variable in peace and conflict dynamics. This article thus develops the concept of "regional peace formation," arguing that the neighbourhood matters either as an enabling or hindering factor for peacebuilding. Based on empirical evidence from Latin America, the Middle East, and sub-Saharan Africa, we show the usefulness of this concept in explaining regional differences.
Keywords: 300; Latin America; Middle East; Sub-Saharan Africa; peacebuilding; conflict; regional organizations